2016
DOI: 10.3389/fpls.2016.00616
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Thiamin Biosynthesis Genes in Rice Increases Leaf and Unpolished Grain Thiamin Content But Not Resistance to Xanthomonas oryzae pv. oryzae

Abstract: Thiamin diphosphate (ThDP), also known as vitamin B1, serves as an enzymatic cofactor in glucose metabolism, the Krebs cycle, and branched-chain amino acid biosynthesis in all living organisms. Unlike plants and microorganisms, humans are not able to synthesize ThDP de novo and must obtain it from their diet. Staple crops such as rice are poor sources of thiamin. Hence, populations that mainly consume rice commonly suffer thiamin deficiency. In addition to thiamin’s nutritional function, studies in rice have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 48 publications
5
77
1
Order By: Relevance
“…In this report, we describe a combined cross-linking and mass spectrometry (MS) (Weisz et al 2016) approach to investigate the binding patterns of NblA in the cyanobacterium Synechococcus elongatus UTEX 2973 (hereafter referred to as Synechococcus 2973) that doubles in abundance in ~ 2 hours and has only one copy of nblA that is sufficient to mediate PBS degradation (Yu et al 2015). In vitro binding assays combined with chemical cross-linking and MS prove that the C-terminal K 52 in NblA binds to the N-terminal T 2 in β-PC.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we describe a combined cross-linking and mass spectrometry (MS) (Weisz et al 2016) approach to investigate the binding patterns of NblA in the cyanobacterium Synechococcus elongatus UTEX 2973 (hereafter referred to as Synechococcus 2973) that doubles in abundance in ~ 2 hours and has only one copy of nblA that is sufficient to mediate PBS degradation (Yu et al 2015). In vitro binding assays combined with chemical cross-linking and MS prove that the C-terminal K 52 in NblA binds to the N-terminal T 2 in β-PC.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the comparison of vitamin B 6 levels in unpolished seeds (1.02 to 3.15 ng mg fresh weight (FW) −1 ) and polished seeds (0.13 to 0.29 ng mg FW −1 ) (Figure b; Table b,c) suggested that vitamin B 6 mainly accumulates in the embryo and/or aleurone layer, corroborating the analysis of total vitamin B 6 content using the yeast bioassay (Figure ). These results are in agreement with previous studies reporting that other essential micronutrients are stored largely in the husk, aleurone and embryo of rice seeds (Kennedy et al ., ; Lucca et al ., ; Bhullar and Gruissem, ; Dong et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Upregulation of single genes in either the thiazole or pyrimidine biosynthetic pathway does not yield rice plants with increased thiamin (Dong et al., ). However, the combined overexpression of key regulatory genes in each pathway in the plants, namely, thi1 and thiC, caused a fivefold increase of thiamin in brown rice that was lost after polishing (Dong et al., ). Using this approach yielded plants that were more susceptible to stress indicating that this approach is not currently viable.…”
Section: Thiamin (Vitamin B1)mentioning
confidence: 99%
“…Rice is the staple food for more than three billion people and provides over half of the calories available in the food supply for over 500 million people in Asia (Dong, Thomas, Ronald, & Goyer, 2016). Rice naturally has low thiamin content, 0.1 mg/100 g brown rice, which is reduced to 0.02 mg/100 g after polishing (USDA, 2019).…”
Section: Biofortificationmentioning
confidence: 99%